The Relationship between Positivity and Fear of Happiness in People Applying to Graduate Programs in Physical Education and Sports Department - TOGO, Osman Tolga; CAZ, Çağdaş (Asian Journal of Education and Training, 2019)
Positivity is a positive concept for both students and teachers and academics. This people' perspectives are influencing many factors. For this reason, a positive point of view is also an important factor. This perspective affects many negative situations. One of these situations is fear of happiness. The aim of the study with this thought is to examine the relationship between positivity and fear of happiness in people applying to the graduate programs of Physical Education and Sports Department. Study sample consists of 38 women and 83 men who applied to the graduate programs of the Department of Physical Education and Sports of Marmara University in the spring semester of 2016-2017 academic year. Data were collected using the 'Positivity Scale' developed by Caprara et al. (2012) and adapted to the Turkish language by Çıkrıkçı et al. (2015). Data were descriptively analyzed using t-test, one-way analysis of variance (ANOVA) and Pearson Correlation test for independent groups. Participants’ positivity and fear of happiness levels do not significantly differ by gender and age. However, there is a moderate negative correlation between their positivity and fear of happiness levels.